مقومات التنميّة الإقتصاديّة والمحافظة عليها في الهدي الربانيّ (Muqawwamat al-tanmiyah al-iqtisadiyah wa-al-muhafazah 'alayha fi al-huda al-rabbani) - Hashi, Abdurezak Abdulahi (The International Institute of Islamic Thought, 2010)
This study uses an analytical approach to present principles of economic growth derived from the guidance of Revelation: Quran and Sunnah. The Study is divided into two themes. The first one deals with principles related to personal and self sufficient means of economic production at the individual and national levels. The second theme deals with principles related to values that govern behaviors necessary for economic growth; such as preserving spiritual values, balancing income and consumption, integrity of financial transactions, avoiding excessive and wasteful expenditure.